Age Gender and Coping Strategies against Parental Gendered Behaviors - Pokharel, Samidha Dhungel (Nurture, 2019)
Inequality between strong and weak, male and female, rulers and ruled has a long history in human society. Scholars, in Nepal are paying more attention to types and degree of gender discrimination rather than the underpinnings and victims’ efforts to eliminate or lessen such discriminatory practices. The objective of this study is to explore how teenage boys and girls cope against parental gendered behaviours. One hundred and twenty-six teenage boys and girls having cross sexed siblings at home were purposively chosen through networking. Data were collected through self-reporting techniques. Open ended questions were asked to the respondents which were categorized under three main themes for the purpose of data analysis. The present study was carried out in Kathmandu metropolitan city. It was found that though many teenage boys and girls resist parental gendered behaviour, significant numbers of them consider such behaviour as normal and easily accept, many others resist against it. Age and gender play influential roles while using coping strategies. It can be concluded that as teenagers grow up, they shift their emotion focused coping to problem solving strategy. Likewise, more girls than boys cope against discrimination emotionally.